The changing ozone depletion potential of N2O in a future climate. Issue 22 (23rd November 2015) - Revell, L. E.; Tummon, F.; Salawitch, R. J.; Stenke, A.; Peter, T.
Abstract: Nitrous oxide (N2 O), which decomposes in the stratosphere to form nitrogen oxides (NOx ), is currently the dominant anthropogenic ozone‐depleting substance emitted. Ozone depletion potentials (ODPs) of specific compounds, commonly evaluated for present‐day conditions, were developed for long‐lived halocarbons and are used by policymakers to inform decision‐making around protection of the ozone layer. However, the effect of N2 O on ozone will evolve in the future due to changes in stratospheric dynamics and chemistry induced by rising levels of greenhouse gases. Despite the fact that NOx ‐induced ozone loss slows with increasing concentrations of CO2 and CH4, we show that ODPN2O for year 2100 varies under different scenarios and is mostly larger than ODPN2O for year 2000. This occurs because the traditional ODP approach is tied to ozone depletion induced by CFC‐11, which is also sensitive to CO2 and CH4 . We therefore suggest that a single ODP for N2 O is of limited use. Key Points: The ozone depletion potential of N2 O (ODP‐N2 O) is sensitive to CO2 and CH4 ODP‐N2 O in 2100 is larger than in 2000 and varies by up to a factor of 2 A single‐valued ODP‐N2 O is of limited use